Great Bear wild : dispatches from a northern rainforest - McAllister, Ian, 1969- (University of Washington Press, 2021)
The Great Bear Rainforest is the fabled region that stretches up the rugged Pacific coast from the top of Vancouver Island to southern Alaska. A longtime resident of the area, award-winning photographer and conservationist Ian McAllister takes us on a deeply personal journey from the headwaters of the Great Bear Rainforest's unexplored river valleys down to where the ocean meets the rainforest and finally to the hidden depths of the offshore world. Along the way, we meet the spectacular wildlife that inhabits the Great Bear Rainforest--in a not-so-unusual week, McAllister quietly observes twenty-seven bears fishing for salmon, three of which are the famed pure white grizzlies, Kermodes. McAllister introduces us to the First Nations people who have lived there for millennia and have become his close friends and allies, and to the scientists conducting groundbreaking research and racing against time to protect the rainforest from massive energy projects.